(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ABSTRACT: This article treats the subject of Glocalization as the concept of an international product designed to satisfy the needs of a local population, and its role in adaptating any globally unified TV format that can be marketed, in any place in the world, to a successfull cloned TV show, by highlighting the process of going from the concept of Globalization to Glocalization and explaining the different concepts related to TV format and cloned TV shows that result from it, and how it actually is a form of adaptation. To finally discuss the important role that Glocalization can play, if used in specially TV Format Industry, in turning a TV format from a basic one marketed in different areas of the world to a successful cloned TV show that is faithful to the original template and reflects the individualities of the local environment. KEYWORDS: Globalization, Cloned TV Shows, TV Format. الملخص يسعى هذا المقال إلى معالجة موضوع العولمة المحلية باعتبارها تقوم على فكرة أن نفس المنتج أو الخدمة العالمية تكيف لتلبية احتياجات السكان المحليين، والوقوف عند دورها في تحويل أي قالب موحد لبرنامج تالفزيوني عالمي يمكن تسويقه في أي رقعة جغرافية من العالم، إلى برنامج تلفزيوني مستنسخ ناجح محليا. وهذا من خلال إلقاء الضوء على الانتقال من مفهوم العولمة إلى العولمة المحلية، وتوضيح مختلف المفاهيم المتعلقة بالبرامج التلفزيونية المستنسخة، وقوالب البرامج التلفزيونية المنبثقة عنها وكيف أنها في حقيقة الأمر عبارة عن تكييف لها. ليتم التوصل في الأخير إلى الدور المفصلي الذي يمكن أن تلعبه العولمة المحلية في حال ما إذا تم الاعتماد عليها في المجال الإعلامي والصناعات التلفزيونية، خاصة صناعة قوالب البرامج التلفزيونية في تحويلها من مجرد قوالب جامدة تسوق إلى أماكن مختلفة من العالم، إلى برامج تلفزيونية مستنسخة ناجحة محليا، تحافظ على قالب البرنامج الأصلي، وتعكس في نفس الوقت سمات وملامح البيئة المحلية التي تعرض فيها. كلمات دالة : العولمة، العولمة المحلية، البرامج التلفزيونية المستنسخة، قالب البرنامج التلفزيوني.